Expression and imprinting of insulin-like growth factor II (IGF2) and H19 genes in uterine leiomyomas - Rainho, C. A.; Pontes, Anaglória [UNESP]; Rogatto, Silvia Regina [UNESP] (Academic Press Inc., 1999)
Genomic imprinting is defined as a gamete of origin-specific epigenetic modification of DNA leading to differential gene expression in the zygote. Several imprinted genes have been identified and some of them are associated with tumor development. We investigated the expression and the imprinting status of IGF2 and H19 genes in 47 uterine leiomyomas. Using allelic transcription assay, we detected the expression of the IGF2 gene in 10 of a total of 15 informative cases. No loss of imprinting, as determined by the finding of biallelic expression, was detected in any case. The expression of H19 gene was detected in 10 of 20 informative cases and the imprinting pattern was also maintained in all of them. Our data suggest that alterations in IGF2 and H19 genes expression by loss of imprinting do not occur in uterine leiomyomas. (C) 1999 Academic Press.
Keywords: genomic imprinting; growth factor; uterine tumors